2014
DOI: 10.3390/su6095785
|View full text |Cite
|
Sign up to set email alerts
|

Rice Ratoon Crop: A Sustainable Rice Production System for Tropical Hill Agriculture

Abstract: Increasing and sustainable production of rice in tropical hill area is facing various problems where rice ratooning can overcome the limitations. In this study; 22 rice entries were transplanted into experimental tank placed in the hill slope following Completely Randomized Design with five replications to asses' agronomic performance of main crop and ratoon crop where Entry 13 demonstrated highest grain yield per plant (42.06 ± 1.2 gm) as main crop, as well as ratoon crop (3.37 ± 0.28 gm); Entry 19 produced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 13 publications
(11 reference statements)
3
20
0
1
Order By: Relevance
“…Ratooning rice is the cultivation practice of having a second harvest in one cropping season, based on the tillers originating from the stubble of the previous main crop. This practice is widely used in China, the United States, Japan, Philippines, India, Thailand and other countries where there are surplus photothermal resources left after one‐season rice (Faruq et al, 2014). The area for ratooning rice in China is about 550,000 ha, mainly distributed in southwest (mainly in Sichuan and Chongqing), central (mainly in Hubei), eastern (mainly in Fujian, Jiangxi, and Anhui), and southern (mainly in Guangxi) China (Duan et al, 2018).…”
mentioning
confidence: 99%
“…Ratooning rice is the cultivation practice of having a second harvest in one cropping season, based on the tillers originating from the stubble of the previous main crop. This practice is widely used in China, the United States, Japan, Philippines, India, Thailand and other countries where there are surplus photothermal resources left after one‐season rice (Faruq et al, 2014). The area for ratooning rice in China is about 550,000 ha, mainly distributed in southwest (mainly in Sichuan and Chongqing), central (mainly in Hubei), eastern (mainly in Fujian, Jiangxi, and Anhui), and southern (mainly in Guangxi) China (Duan et al, 2018).…”
mentioning
confidence: 99%
“…In this phase, it covers the early development of panicles (40-50 days after planting), fulfilling the phase (50-60 days after planting), and flowering (60-80 days after planting). A research by Faruq et al (2014) showed that ratoon paddy can be harvested in 90 days, while the study conducted by Setiawan et al (2014) revealed that it can be harvested in 96 days. This situation is characterized by the formation and growing of panicles.…”
Section: Ratoon Paddy Cultivation Systemmentioning
confidence: 99%
“…Paddy plants usually need -20 cm to -30 cm water level from the ground surface. It is related to the plant roots in penetrating the soil to uptake water for the plant (Faruq, Taha, & Prodhan, 2014). So far, this ratoon paddy cultivation technique has not been developed in the tidal lowland area.…”
Section: Introductionmentioning
confidence: 99%
“…The labor and seed inputs for ratoon rice cropping were reduced by 29% and 52%, respectively, compared with double cropping systems [3,4]. However, many studies have concluded that ratoon rice exhibits a low-yield performance, approximately 40-60% that of the main crop [5,6]; thus, low and unstable grain yield has limited the wide adoption of ratoon cropping.…”
Section: Introductionmentioning
confidence: 99%